Relativistic convergent close-coupling calculation of inelastic scattering of electrons from cesium - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (American Physical Society, 2014)
We present fully relativistic convergent close-coupling calculations of differential cross sections, spin-asymmetries, and Stokes parameters for inelastic electron-cesium scattering at intermediate energies. Comparison is made with the differential cross section and spin asymmetry measurements of Baum et al. [Phys. Rev. A 70, 012707 (2004)] and the Stokes parameter measurements of Slaughter et al. [Phys. Rev. A 75, 062717 (2007)]. Comparison is also made with previous semirelativistic and nonrelativistic theories. With a relatively high atomic number for cesium (Z=55) we find surprisingly excellent agreement between the relativistic, semirelativistic, and nonrelativistic theories for most observables. The overall agreement with the measurements is very good, with isolated discrepancies for some observables.